Dimensions of the Parent–Child Relationship: Effects on Substance Use in Adolescence and Adulthood. (16th April 2019) - Mak, Hei Wan; Iacovou, Maria
Abstract: Background : Several studies have uncovered a relationship between parenting styles and the likelihood that adolescents use tobacco, alcohol or illegal drugs. Objectives : This paper extends existing research in two ways. First, we consider a longer time-frame, investigating the relationship between parenting in adolescence and substance use in adulthood. Second, we explore the pathways by which this relationship is expressed, in particular the extent to which the relationships in question are mediated by age at first use and depression. Methods : Our analysis is based on data from the National Longitudinal Study of Adolescent Health (Add Health), N  = 2954, and is conducted using structural equation modeling (SEM). We consider warmth and control as distinct dimensions of parenting, as well as a typology of parenting which combines the two dimensions. Results : Warmth is associated with reduced risks of problem substance use in adulthood, via reduced risks of early initiation and a lower risk of depression. Parental control also has a protective effect via reduced risks of early initiation, but this is offset by a detrimental effect on depression, particularly in the case of older adolescents. We also find that indulgent parenting is not associated with extra risk of any kind compared with the authoritative style, whereas authoritarian and neglectful styles are. Conclusions/Importance : The nexus of relationships which we uncover has implications for policy aimed at reducing substance use in the longer term, suggesting that initiatives to promote warm and responsive parenting may be most effective in reducing the risks of later substance use problems.